Scholars’ YouTube channels: content analysis of educational videos - Martinho, Mariana (2012)
YouTube is a Web 2.0 platform of distributed video sharing, widely used by students, universities and scholars. This article looks into the YouTube channels set by three scholars - Dave Cormier, Wendy Drexler and Michael Wesch -, whose research interests are linked to technology enhanced learning. The focus of analysis is on the sample of videos each scholar uploaded and categorized as “education” in their YouTube channels. The data collected from the content analysis allows to understand what content is being shared and with what approach. The overall results suggest that those scholars who have a channel as personal, or as officially linked to the university, share videos produced as a result of their work as scholars, some of which even share copyright with the institution. All the videos address similar concepts and ideas regarding the integration and use of technology in education, but the approach to present them differs.